File integrity checking - Motara, Yusuf Moosa (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
This thesis looks at file execution as an attack vector that leads to the execution of unauthorized code. File integrity checking is examined as a means of removing this attack vector, and the design, implementation, and evaluation of a best-of-breed file integrity checker for the Linux operating system is undertaken. We conclude that the resultant file integrity checker does succeed in removing file execution as an attack vector, does so at a computational cost that is negligible, and displays innovative and useful features that are not currently found in any other Linux file integrity checker.
Keywords: Linux; Operating systems (Computers); Database design; Computer security